Risk factors for the development of hospital infections in the intensive care units - Mijović Biljana; Janković Slavenka M.; Maksimović Nataša; Marinković Jelena M. (Vojnosanitetski Pregled)
Background. Patients admitted to intensive-care units (ICU) are at a high risk of nosocomial infections (NI) due to susceptibility associated with severity of their condition, but also the invasive medical procedures they undergo. Aim. To determine the frequency of NI at the ICU of the General Hospital Užice, and to identify the risk factors for their development. Methods. A prospective surveillance study of NI, conducted between June 27 and December 31 2001, included 914 patients who spent at least 24 hours in the ICU (total of 2 615 days). The surveillance of NI in the ICU was carried out daily. Follow-up period covered the time from the ICU admission to 48 hours after the ICU discharge. To assess risk factors for NI, we performed a case-control study. The variables measuring of extrinsic and intrinsic risk factors for NI were collected. Results. In a six-month prospective surveillance study, the incidence of NI was 16.7% or 58.5 per 1,000 patient-day, respectively. The most frequent were the infections of the surgery wounds (32.6%), urinary tract infections (23.5%), and infections of the blood (7.1%). The identified independent risk factors for NI were: surgical intervention (OR = 5.74; CI = 2.01-16.41), endotracheal tubes (OR = 3.40; CI = 1.07-10.89), cystoscopy (OR = 2.35; CI = 1.38- 4.02), obesity (OR = 1.98; CI = 1.27-3.11), and the duration of the infusion (OR = 1.34; CI = 1.23-1.46). Conclusions. The most important risk factors for NI at ICU were surgical interventions and endotracheal tubes.